Pendampingan Penyusunan Sistem Rekrutmen pada Karyawan Pabrik Demang Jaya Wonokerto - Faizatun Nikmah; Uswatun Karimah; Sinollah; Imron Rosyadi Hamid; Rr. Hesti Setyodyah Lestari (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2025)
This article discusses assistance is preapring recrutmen system criteria for Demang Jaya Wonokerto cigarette factory employes. This research aims to increas effectiveness and efficiency in the employe recrutment process at the cigarette factory. The method used in this research is a case study and direct observation of the existing recrutmen process. The research result show that assistance in preparing recrutment system criteria can improve the quality of employees recruited and reduce erros in the selection process. It is hoped that the results of this research can make a positive contribution to Demang Jaya Wonokerto cigarette factory in improving employe performance and productivity.